Analysis The Level Aggressiveness of Karate Athletes on Kata Number - Miftah Fariz; Didi Sunadi; Hendra Nugraha; Giri Prayogo (Universitas PGRI Palembang, 2023)
Karate is one of the oldest martial arts originating from Japan and has developed rapidly in Indonesia. Karate itself is a martial art that has Chinese martial influences and kempo. A karate martial artist must certainly have a good level of aggressiveness so that later it can be used in a match that requires a high level of success. The purpose of this study was to determine the level of aggressiveness of karate athletes in word numbers. This study was conducted using quantitative descriptive methods using closed questionnaire techniques. The population in this study is PP INKAI Prestasi athletes in Jakarta totaling 30 people. Determination of samples in this study through non-probability sampling techniques (purposive sampling) so that it became 15 people in accordance with the criteria desired by the researcher. The results of this study show that the level of aggressiveness of karate athletes in word numbers is included in the medium category because word numbers are numbers that compete for compactness, regularity of motion and discipline of movement. However, this can be a further input to further increase the aggressiveness of word number karate.